New approaches for dissemination and implementation of sport-science research outcomes - Pyne, D. B.; Périard, J. D. (International Journal of Sports Physiology and Performance, 2023)
Readers of the International Journal of Sports Physiology and Performance (IJSPP) will be familiar with the requirement to highlight the practical applications of a study. Typically, the practical application section comprises a short series of statements detailing how the outcomes can be applied in one or more sport settings (eg, field or court training, in the gym, competitions, recovery, and/or more broadly in athlete-development pathways) for the direct benefit of the athlete and/or coach. However, the value of research can be realized in other practical settings or more broadly for the benefit of others, in addition to the immediate beneficiaries.